LINGUOCULTURAL FEATURES OF PROPER NAMES IN THE NOVEL “OTAMDAN QOLGAN DALALAR” (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the linguocultural features of proper names in the work Otamdan qolgan dalalar. The study analyzes proper names in a literary text not only as nominative units, but also as important linguocultural codes that express national culture, historical memory, and social consciousness. The semantic, symbolic, and conceptual functions of toponymic, anthroponymic, as well as historically and ideologically marked proper names found in the novel are identified. The research results demonstrate that through proper names the Uzbek people’s attitude toward land, ancestral heritage, intergenerational continuity, and national mentality are artistically expressed. The article is of significant scholarly value for studying Uzbek literary texts from a linguocultural perspective.